Stock Market Bubble- Investigate Cause and Effect of Stock Market Bubbles and Examine How Bubbles can be Identified and Prevented - Patel, Prisha (Integrated Journal for Research in Arts and Humanities, 2024)
When asset prices surge far beyond their true worth, a phenomenon known as a stock market bubble occurs, and it is frequently followed by a severe decline in value. Using statistical tools such as SPSS and Excel, this study delves into the issue of stock market bubbles. It specifically examines the top 100 businesses listed on the Bombay Stock Exchange (BSE) in India. Using examples such as the 1929 Wall Street Crash, the late 1980s Japanese asset price bubble, and the late 1990s dot-com boom, this study seeks to understand the causes of bubbles and how they affect investors and the financial system as a whole. Market mood, trading volumes, price-to-earnings ratios, and valuation trends are some of the early warning indicators that are analyzed using quantitative approaches in the study. While non-stationarity does not prove the existence of a bubble on its own, it does raise the possibility that prices are trending without undergoing a mean-reverting process, which is a hallmark of bubbles. This study intends to shed light on how to improve financial stability in the Indian stock market and reduce the risks of speculative bubbles by analyzing these powerful corporations.